Precarious labor geographies in globalized agriculture. Feminization, ethnicity and migrations - Valdés Subercaseaux, Ximena (Investigaciones Geográficas, 2023)
This article analyzes different modalities that the wage inclusion of seasonal workers acquires in the temporary agricultural work of fruits and vegetables. It highlights geographic mobility, border spaces and labor transit, the feminization process, of different origins, migrations and transmigrations of the labor force in the production of fresh fruits and vegetables. The problem raises concerns about the consequences of employment for workers in the globalized intensive agriculture, knowing that territorial displacements over variable distances produce long workings hours and poor working conditions, which leads to typify this work as precarious employment. We dig into different countries’ realities to show that, despite the different levels of development, globalized agriculture operates under similar conditions in several cases, this is, homogenizing the use of local and foreign labor force, feminine and masculine and indigenous, who hardly count with any social rights in a scenario that manifests in how rar the deprivation of rights is an expression of the new social issue imposed by “globalization from below” (Tarrius, 2007). The study is based on numerous investigations on seasonal workers in Chile that the author has carried out within the framework of Fondecyt projects.